Predictive significance of standardized uptake value parameters of FDG-PET in patients with non-small cell lung carcinoma - Duan,X-Y. (2015)
18F-fluoro-2-deoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) is widely used to diagnose and stage non-small cell lung cancer (NSCLC). The aim of this retrospective study was to evaluate the predictive ability of different FDG standardized uptake values (SUVs) in 74 patients with newly diagnosed NSCLC. 18F-FDG PET/CT scans were performed and different SUV parameters (SUVmax, SUVavg, SUVT/L, and SUVT/A) obtained, and their relationship with clinical characteristics were investigated. Meanwhile, correlation and multiple stepwise regression analyses were performed to determine the primary predictor of SUVs for NSCLC. Age, gender, and tumor size significantly affected SUV parameters. The mean SUVs of squamous cell carcinoma were higher than those of adenocarcinoma. Poorly differentiated tumors exhibited higher SUVs than well-differentiated ones. Further analyses based on the pathologic type revealed that the SUVmax, SUVavg, and SUVT/L of poorly differentiated adenocarcinoma tumors were higher than those of moderately or well-differentiated tumors. Among these four SUV parameters, SUVT/L was the primary predictor for tumor differentiation. However, in adenocarcinoma, SUVmax was the determining factor for tumor differentiation. Our results showed that these four SUV parameters had predictive significance related to NSCLC tumor differentiation; SUVT/L appeared to be most useful overall, but SUVmax was the best index for adenocarcinoma tumor differentiation.